2021
DOI: 10.3389/fnins.2021.805679
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Restraint Habituation for Awake Functional Magnetic Resonance Imaging Combined With a Sparse Imaging Paradigm Reduces Motion Artifacts and Stress Levels in Rodents

Abstract: Functional magnetic resonance imaging, as a non-invasive technique, offers unique opportunities to assess brain function and connectivity under a broad range of applications, ranging from passive sensory stimulation to high-level cognitive abilities, in awake animals. This approach is confounded, however, by the fact that physical restraint and loud unpredictable acoustic noise must inevitably accompany fMRI recordings. These factors induce marked stress in rodents, and stress-related elevations of corticoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 113 publications
1
12
0
Order By: Relevance
“…Furthermore, mean FCM concentrations for both male and female on the last day of MRI habituation appear below that of pre handling levels (Figure 7A). This is consistent with other groups who reported decreased FCM concentration levels after several days of awake MRI training (King et al, 2005;Tsurugizawa et al, 2020;Russo et al, 2021). Lastly, during our MRI habituation period, both male and female mice were able to recover, maintain and increase their body weight.…”
Section: Discomfort Stress and Anxiety In Male And Female Micesupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, mean FCM concentrations for both male and female on the last day of MRI habituation appear below that of pre handling levels (Figure 7A). This is consistent with other groups who reported decreased FCM concentration levels after several days of awake MRI training (King et al, 2005;Tsurugizawa et al, 2020;Russo et al, 2021). Lastly, during our MRI habituation period, both male and female mice were able to recover, maintain and increase their body weight.…”
Section: Discomfort Stress and Anxiety In Male And Female Micesupporting
confidence: 92%
“…For most labs, however, scanner resources are too scarce to include an actual MRI scanner in the habituation so we opted for a habituation protocol using a simulated scanner environment only to ensure our study is relevant to as many labs as possible. For future work it may be beneficial to include resting days as implemented in similar studies (Russo et al, 2021). However, our FCM data shows that if habituation is not maintained stress of handling increases again (Post time point in Figure 7A, both sexes).…”
Section: Awake Mouse Magnetic Resonance Imaging Habituation Protocolmentioning
confidence: 99%
“…Efforts are presently underway to create protocols aimed at optimizing habituation to the MRI environment and mitigating the stressful effects of head fixation, body restraint and noise via a gradual and incremental habituation protocols (63)(64)(65)(66). Some of these studies have shown that these procedure can result in stress-related corticosterone levels comparable to pre-handling levels in both mice (57) and rats (67). In the latter species, thanks to a sparse MRI sequence tuned to reduce acoustic stress, animals could even discriminate auditory stimulation from the background scanner noise (67).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Despite common functional connectivity between awaked and lightly anesthetized state ( Grandjean et al, 2020 ; Tsurugizawa and Yoshimaru, 2021 ), fMRI signal changes to the physiological stimuli are significantly disturbed by the anesthetic ( Peeters et al, 2001 ; Tsurugizawa et al, 2010 , 2016 ; Aksenov et al, 2015 ; Tokunaga et al, 2021 ; You et al, 2021 ). As an alternative, awake mouse fMRI is developed using habituation training to reduce stress during MRI experiments ( Tsurugizawa et al, 2013 , 2020 , 2021 ; Bergmann et al, 2016 ; Yoshida et al, 2016 ; Madularu et al, 2017 ; Chen et al, 2020 ; Russo et al, 2021 ). Although the habituation protocol needs refinement to reduce stress efficiently ( Low et al, 2016 ), awake fMRI can be an essential tool to bridge the human MRI and rodent MRI.…”
Section: Discussionmentioning
confidence: 99%